Long QT syndrome and life threatening arrhythmia in a newborn: molecular diagnosis and treatment response. Issue 1 (15th December 2003) - Schulze-Bahr, E; Fenge, H; Etzrodt, D; Haverkamp, W; Mönnig, G; Wedekind, H; Breithardt, G; Kehl, H-G
Abstract : Intrauterine and neonatal manifestations of congenital long QT syndrome are associated with a high cardiac risk, particularly when atrioventricular block and excessive QT prolongation (> 600 ms 1/2 ) are present. In a female newborn with these features, treatment with propranolol and mexiletine led to complete reduction of arrhythmia that was maintained 1.5 years later. High throughput genetic analysis found a sodium channel gene (LQT3) mutation. Disappearance of the 2:1 atrioventricular block and QTc shortening (from 740 ms 1/2 to 480 ms 1/2 ), however, was achieved when mexiletine was added to propranolol. This effect was considered to be possibly genotype related. Early onset forms of long QT syndrome may benefit from advanced genotyping.